2012
DOI: 10.1088/1742-6596/377/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

High - pressure synchrotron x-ray diffraction study of RMnO3(R = Eu, Gd, Tb and Dy) upto 50 GPa

Abstract: We have carried out synchrotron based high-pressure x-ray diffraction study of orthorhombic EuMnO 3 , GdMnO 3 , TbMnO 3 and DyMnO 3 up to 54.4, 41.6, 47.0 and 50.2 GPa, respectively. The diffraction peaks of all the four manganites shift monotonically to higher diffraction angles and the crystals retain the orthorhombic structure till the highest pressure. We have fitted the observed volume versus pressure data with the Birch-Murnaghan equation of state and determined the bulk modulus to be 185 ± 6 GPa, 190 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The anomalies can be explicated by comparing the fitting pressure data of the E3M3 structure tabbed by blue stars in the same panel, calculated with a second-order B-M EOS given below , where V 0 and B 0 have been obtained from eq . The fitting values marked by blue stars are in conformity with the previous experimental reports, , which verified the reliability of the theoretical methods. The deviation of external pressure from the fitting line is caused by the transition from E3M3 to E2M4 under high pressure (positive), which releases some pressure by changing the cell shape and internal distortions to respond to the decrease of volume.…”
Section: Resultssupporting
confidence: 89%
“…The anomalies can be explicated by comparing the fitting pressure data of the E3M3 structure tabbed by blue stars in the same panel, calculated with a second-order B-M EOS given below , where V 0 and B 0 have been obtained from eq . The fitting values marked by blue stars are in conformity with the previous experimental reports, , which verified the reliability of the theoretical methods. The deviation of external pressure from the fitting line is caused by the transition from E3M3 to E2M4 under high pressure (positive), which releases some pressure by changing the cell shape and internal distortions to respond to the decrease of volume.…”
Section: Resultssupporting
confidence: 89%
“…[16]. This can most probably be accounted for by the pressure-transmitting medium used in that study (ethanol-methanol instead of helium), which produces very strong deviatoric stress above 054104-2 10 GPa.…”
Section: Resultsmentioning
confidence: 81%
“…Recently, we reported synchrotron x-ray diffraction and Raman spectroscopy studies of GdMnO 3 under pressure up to 55 GPa and showed evidence for a first-order structural transition accompanied by an insulator-to-metal transition around 50 GPa [15]. In contrast, Muthu et al [16] have not observed any structural transition at all up to 50 GPa for A = Eu, Gd, Tb, and Dy.…”
Section: Introductionmentioning
confidence: 88%